Late Quaternary vegetation reconstruction from the Eastern Arc Mountains, Tanzania - Mumbi, C. T.; Marchant, R.; Hooghiemstra, H.; Wooller, M. J. (Quaternary Research, 2008)
Pollen, spore, macrofossil and stable isotope (C and N) analyses from a 266-cm sediment core collected from a swamp on the Eastern Arc Mountains, Tanzania, are used to reconstruct vegetation and environmental history. An estimated time scale based on five C-14 ages records approximately 38,000 yr. This palaeorecord is the first from this biodiversity hotspot and importantly extends through the last glacial maximum (LGM). The altitudinal transition from montane to upper montane forest shifted from 1700-1800 in (38,000 C-14 yr BP) to 1800-1900 in (35,000-29,000 C-14 yr BP). From 29,000 to 10,000 C-14 yr BP, it shifted from 1850-1950 in across the LGM to 1750-1800 in (during 10,000-3500 C-14 yr BP), and to present-day elevations at 2000 in during the last 3500 C-14 yr BP. The relative ecosystem stability across the LGM may be explained by the Indian Ocean's influence in maintaining continuous moist forest cover during a period of East African regional climate aridity. During the late Holocene, presence of abundant coprophilous fungi and algal blooms demonstrates increasing human impact. Neurospora spores indicate frequent fires, coinciding with clear signals of decline in Podocarpus and Psychotria trees that possibly represent selective logging. (C) 2007 University of Washington. All rights reserved.
id: 1836; 285PB Times Cited:6 Cited References Count:105Y